Exploring the Impact of Marketing Mix on Consumer Purchasing Decisions and Consumer Satisfaction: Case Study of Fried Shallots in Malang City - Alisa Durrotul Fuadah; Budi Setiawan; Syafrial Syafrial (Eduvest - Journal of Universal Studies, 2024)
Shallots are easily damaged and require proper post-harvest handling to extend their shelf life and increase their economic value. Agro-industry can turn shallots into fried onions that are long-lasting and ready for long-term consumption. The development of a small shallot industry needs to consider consumer behavior to identify market preferences. This research uses a quantitative descriptive approach and the SEM-PLS method to analyze the factors that influence the marketing mix on purchasing decisions and satisfaction. The results show that marketing mix aspects such as product, price, promotion, people, process, and physical evidence have a positive impact on purchasing decisions and consumer satisfaction of fried shallots in Malang City. The strategy that companies can implement is to focus on improving product quality, affordable prices, effective promotions, good customer service, easy purchasing processes, and convincing physical evidence so that they can increase purchasing decisions and consumer satisfaction.